Bringing contemporary ethics down to earth for generation Z: A study of moral values in digital disruption and its implications for educational leadership - Rosmita Rosmita; Listiawati Susanti; Zulamri Zulamri; Mardhiah Rubani; Achmad Ghozali (Kuras Institute, 2026)
Purpose – This study addresses the urgent need to understand and apply ethical principles for Generation Z in the context of rapid digital disruption. With the proliferation of social media, artificial intelligence, and algorithm-driven interactions, young people face unique moral challenges, including empathy erosion, moral relativism, the spread of misinformation, and normalization of symbolic violence online. The purpose of this research is to explore how moral values can be recontextualized so they remain meaningful, practical, and normative for Generation Z, empowering them to navigate digital environments responsibly and thoughtfully. Method – The research employs a qualitative-descriptive literature review approach. Primary sources include contemporary ethical theories, studies in digital sociology, and scholarship on moral education. Data collection involved selecting relevant academic articles, books, and reports addressing ethics in digital contexts. Analysis was conducted through thematic coding, comparing ethical frameworks with observed trends in Generation Z’s digital behavior, and synthesizing insights on applicable strategies for moral development in online spaces. Findings – The study finds that contemporary ethics for Generation Z should be grounded in dialogical, contextual, and participatory approaches. Key values identified include digital responsibility, social empathy, justice, critical literacy, and awareness of the consequences of online actions. Generation Z is not merely a target for moral instruction but an active participant capable of shaping ethical frameworks based on lived digital experiences. Effective moral development requires integration of ethics into educational curricula, family guidance, and digital ecosystem design, ensuring that ethical principles are both adaptive and firmly rooted in normative foundations